Florian Siegl : Materials on Forest Énets, an indigenous language of northern Siberia - Léonard, Jean Léo (Études finno-ougriennes, 2016)
Nous n’irons pas par quatre chemins pour commencer cette recension : l’ouvrage de Florian Siegl sur le samoyède « énets de la forêt », langue désormais résiduelle dans les localités de Potapovo et Dudinka, dans la péninsule de Tajmyr, en Sibérie septentrionale) fera date, non seulement pour la linguistique ouralienne et les études samoyèdes, mais également pour la linguistique générale et le paradigme de la « Documentary Linguistics » ou Documentation des Langues en Danger (DLD) – cf. Austin . We will not start by four tracks: Florian Siegl’s book on the ‘forest nose’ samoydo, a language which is now residual in Potapovo and Dudinka on the Tajmyr peninsula in Northern Siberia) will be dated, not only for hurricanes and samoya studies, but also for the general language and paradigm of ‘Documentary Linguistics’ or Documentation des Langugues en Danger (DLD) – cf. Austin.